Social intrapreneurship: exploring tensions and paradoxes of embedded agency. - Herniman, John (Cranfield University, 2021)
Unmet societal needs require social innovation from various actors and agents. Social intrapreneurs, the corporate sibling of social entrepreneurs, are relatively understudied in management and organisational academic literature. Contemporary empirical studies of social intrapreneurship have focused on the enterprise (context) and the nature and results (outcome) of the social intrapreneurial activity. The academic literature contains fewer descriptions of social intrapreneurs at an individual level. The research is often heterogeneous and fluid in definition, and sometimes contradictory. This discourse utilises social innovation studies, organisational studies and theories of innovation, paradox and embedded agency (neo-institutional theory) to augment the limited social intrapreneurship literature. Research questions are formed based on limited extant literature on mechanisms describing social intrapreneurs as individual actors. This research provides empirical insight into the challenges and mitigations, experienced and enacted, from the perspective of a social intrapreneur within for-profit multinational organisations. A social constructivist stance is utilised in developing an exploratory understanding from semi- structured interviews with 62 social intrapreneurs in MNCs. To address the primary research question, “what tensions do social intrapreneurs experience?” This research contributes to organisation studies by proposing empirically derived frameworks of tensions experienced and navigations enacted by social intrapreneurs, as described by social intrapreneurs. Complementary to these frameworks, this research contributes an exploratory perspective on the interplay between tensions and navigations with role formalisation of social intrapreneurs with respect to social action and innovation. In practice, social intrapreneurs and organisations may gain insights into frameworks of enablers and disablers of social innovation.
Keywords: Multinational company; social entrepreneur; institutional entrepreneur; paradox theory; social innovation; enablers; disablers